The Importance of Integrating Effective Teaching Methods in Business English Classroom - Tamar Dolidze; Anna Abesadze; Brandon Harding; Paola Clara Leotta (European Scientific Journal, ESJ, 2023)
The paper highlights the importance of integrating effective methods in teaching English for Specific Purposes, in particular Business English.  According to the survey, which includes the contribution from 48 BE instructors worldwide, the article demonstrates the significance of lexical approach, task-based and project-based learning by evaluating the outcomes of integrating them in teaching practice and beyond. The results once again confirmed the hypothesis that task-based learning, lexical approach and project-based learning are the most effective teaching methods in BE classroom. The survey consisted of both open and close-ended questions and aimed at voicing the opinion of BE Course Instructors globally. The target audience was exposed to the above-mentioned teaching methods.  At the same time, the survey provides recommendations for novice BE Lecturers on how to ensure maximal approximation to the authentic environment via practicing most useful teaching methods and making the learning process more result-driven, engaging and enjoyable.